Victim’s posture and protective clothing changes the approach in an edged-weapon attack - Carr, Debra J.; Mahoney, Peter F.; Godhania, K.; Cowper, Elizabeth J.; Malbon, Christopher (International Ballistics Society, 2017)
Diverse groups of people use edged-weapons (i.e. knives, spears, swords) professionally. The training received affects how the edged-weapon is used and the area of the body targeted. There is a growing body of information available on the internet which is aimed at the training individuals in offensive knife attacks. This poster aims to raise awareness of this issue and highlight how a trained individual modifies an attack sequence depending on their victim’s posture and the protective clothing worn. A male trained in the Filipino martial arts discipline of Eskrima performed attack techniques on a static mannequin covered with a long sleeved upper body garment and leggings, a police custodian helmet and a HG1 + KR1 police body armour. In some simulated attacks the target was also dressed in a police high-visibility tactical vest on top of the body armour. High-speed video was used to capture each simulated attack and the impact location on the torso recorded using ultra-violet sensitive liquid applied to the weapon. Target posture was modified by adjusting the arm position of the mannequin. In a second series of experiments a PermaGel™ male target torso was used so that penetrating damage could be assessed. Data collected identified the change of attack due to victim’s posture and vulnerability of the neck, underarm area and groin